2008
DOI: 10.1159/000124285
|View full text |Cite
|
Sign up to set email alerts
|

Lack of iNOS Impairs Endothelial Function in Endothelin-1 Transgenic Mice

Abstract: Background: Endothelin-1 (ET-1) is one of the most potent biologic vasoconstrictors. Nevertheless, transgenic mice overexpressing ET-1 exhibit normal blood pressure. We hypothesized that in states of ET-1 overproduction, the lack of counterregulatory mediators such as nitric oxide (NO), produced by the inducible NO synthase (iNOS), may critically impair endothelial function and may result in blood pressure elevation. Methods: We generated crossbred animals of ET transgenic mice (ET+/+) and iNOS knockout mice (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
2
2
0
Order By: Relevance
“…Compared to the normotensive wild type and ET+/+, the crossbred ET+/+ eNOS KO have a significantly elevated blood pressure. This is also seen in ET+/+ inducible NOS KO crossbreds [11] which corroborates the hypothesis that the NO system counterregulates the ET overexpression in the ET-1 transgenic model leading to a normotensive phenotype.…”
Section: The Transgenic Animal Modelssupporting
confidence: 80%
“…Compared to the normotensive wild type and ET+/+, the crossbred ET+/+ eNOS KO have a significantly elevated blood pressure. This is also seen in ET+/+ inducible NOS KO crossbreds [11] which corroborates the hypothesis that the NO system counterregulates the ET overexpression in the ET-1 transgenic model leading to a normotensive phenotype.…”
Section: The Transgenic Animal Modelssupporting
confidence: 80%
“…Studies in clinics have shown that administration of big ET-1 results in improved vasoconstriction and increased formation of ET-1 in patients with atherosclerosis (Bo¨hm et al 2002). Studies carried out in animals have showed that in transgenic mice overexpressing human ET-1 results in impaired endothelium-dependent (Quaschning et al 2008). The results of the present study showed that endothelium-dependent vasorelaxation was impaired concomitantly with increase of ET-1 and MDA levels in hypercholesterolemic rabbits.…”
Section: Discussionsupporting
confidence: 61%
“…There is substantial evidence to suggest that endogenous ET-1 is also involved in the development of endothelial dysfunction in atherosclerosis (Bo¨hm et al 2002;Quaschning et al 2008). Studies in clinics have shown that administration of big ET-1 results in improved vasoconstriction and increased formation of ET-1 in patients with atherosclerosis (Bo¨hm et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, no alterations in oxidative stress biomarkers were detected in any of the dietary protocols. In transgenic mice overexpressing human endothelin-1 (ET-1), the knockout of iNOS resulted in impaired endothelium-dependent vasodilation [51]. Although the increased expression of iNOS was thought to contribute to the occurrence of cardiogenic shock in individuals with myocardial infarction, iNOS inhibitors did not show beneficial effects in this group of individuals.…”
Section: Discussionmentioning
confidence: 99%